School Readiness in Online Learning: Impact of Implementation of Education Policy - Romy Hermawan (Jurnal Pendidikan dan Pengajaran, 2022)
The impact of the Covid-19 pandemic has become a global issue that is of particular concern to the world of education, including in Indonesia. This study aims to analyses the readiness of online learning policies in school units since the Covid-19 pandemic broke out in Indonesia. This study used a survey method with a quantitative approach which has distributed questionnaires to 367 elementary schools and 64 junior high schools. Data analyzes use describes the results of statistics on questionnaires that have been distributed to schools. The results of this study indicate that as many as 365 (99.46%) elementary schools choose online learning. Meanwhile, for junior high schools, 64 (96.88%) schools chose online learning. However, the implementation of online learning has obstacles that should be a concern. The mental health and socio-economic conditions of the community to pay for their children's schooling are increasing while currently experiencing a health and economic crisis. This is the government's next effort to evaluate policies to not only respond to the Covid-19 pandemic but also to overcome new problems that arise with online learning policies.